Ending War, Building Peace - Blanchard, Lynda-ann; Chan, Leah (Sydney University Press, 2009)
The US-led invasion and occupation of Iraq led to more than a million people being killed, displaced five million from their homes and shattered countless more lives. It was a colossal, premeditated war crime. Leaders of governments in the countries responsible for this enormity seek to minimise and forget about it: to 'move on'. We must not let them, because they want to retain the option of making the same political decisions, condemning more innocent people to death, somewhere else in the future. Contributors to this book are united in saying: never again. They examine how and why this unmitigated disaster for humanity was allowed to happen, and how we can prevent it being repeated. And they imagine more peaceful ways to engage with conflicts and crises in times to come. It raises a question: what will you do to help end war and build peace?